Tectonostratigraphic characterization of the adjacent portion to the São Vincente earthquake epicenter in the santos basin - Schweig, Camila [UNESP]; Dourado, João Carlos [UNESP]; de Souza, Iata Anderson [UNESP] (Sociedade Brasileira de Geofisica, 2015)
The São Vicente earthquake, which had occurred in the Santos Basin, approximately 200 km from São Vicente city, São Paulo state in 2008, was well detected in the global network, allowing a good determination of their focal mechanisms and associated nodal planes, sub-horizontal (strike 82°) and subvertical (strike 341°). Understanding seismic data, geological and geophysical data have been necessary to determine which nodal plane is the earthquake generating fault. Gravity anomaly maps and structural contour maps allowed defining structures on regional scale. It has been observed that the epicenter is located in the high portion of the slope next to a canyon feature and the aligned graben occurrence, the Merluza Graben, coincident with Capricorn Lineament occurrence. The seismic sections have shown that in the direction of the sub-horizontal plane, less significant faults have occurred when compared to the direction of subvertical plane where there have been faults that intersect from the Basement layer to the Cenozoic layers, indicating that they were activated or reactivated on neotectonic events. The Mapping of a normal antithetic fault to the NS direction quite significant along the data, have suggested that a horizontal trend of this fault plane might bind to the earthquake hypocenter.
Keywords: Intraplate seismicity; Passive margin; Seismic